The Dynamics of Colonial Libraries in the Dutch East Indies: Governmental Roles and Management Challenges (1887-1918) - Putra, Purwanto; Purnamayanti, Arnila; Nurdiansyah, Aulia; Maryani, Eri (JURNAL JAWI, 2026)
This article examines the role of the colonial government in the management of libraries in the Dutch East Indies and traces the development of libraries between 1887 and 1918. The study focuses on official reports and historical records concerning library administration, public engagement with library services, and the evolution of library provision within the colonial context. Employing the historical method, the research utilizes primary sources retrieved from digital archives, particularly Delpher and the Leiden University digital collections. The analysis follows the stages of topic selection, source collection and verification, historical interpretation, and historiographical writing. The findings reveal that the Dutch East Indies government played a relatively limited role, primarily confined to administrative oversight and basic regulatory functions, while facing significant constraints, including inadequate funding and a shortage of professionally trained librarians. A comparison with the Netherlands highlights substantial disparities in institutional support and service quality. Evidence from Semarang in 1917–1918 illustrates these inequalities: the Public Reading Room (Openbare Leeszaal), established by the Hogere Burgerschool (H.B.S.) and the Semarang branch of the Algemeen Nederlandsch Verbond (ANV), was initially staffed by a librarian and later expanded to include an assistant librarian and two indigenous clerks. Indigenous personnel were assigned exclusively to clerical positions rather than professional librarian or assistant librarian roles, reflecting the hierarchical structure of the colonial administration. Furthermore, low levels of public interest and the unequal distribution of resources further constrained the growth of libraries throughout the Dutch East Indies. The study concludes that, despite efforts to improve access to library services, no substantial transformation occurred, and colonial libraries continued to develop only to a limited extent.